Estado, burguesia e legislação trabalhista brasileira no limiar dos anos 30: Notas para uma discussão - de Moraes, Rafael Vicente [UNESP] (My University, 2009)
The creation and implementation of Brazilian labor laws during the 1930s gave rise to important political debates. The various stakeholders - the state, the bourgeoisie, and workers - each with their own social project, had forged mechanisms designed to protect their own interests. Within this framework, this article addresses the arguments regarding the Expulsion of Foreigners Act (1907), the Dois Terços(Two-thirds) Act (1930), and the Unionization Act (1931). These acts provide clear evidence that the growth of state interventionism was accompanied by tensions and changes, and that the labor legislation was not simply the 'gift' of a Corporate State.
The State, the Bourgeoisie, and Brazilian labor law in the early 1930s: Notes for discussion
Keywords: Brazilian Bourgeoisie; Labor laws; State; Working-class movement